PEMIKIRAN PENDIDIKAN ISLAM SYED MUHAMMAD NAQUIB AL-ATTAS (Tinjauan Paradigmatik dan Implementatif Konsep ta’dib dalam pembelajaran Agama Islam pada tingkat SMA/MA) - Putri Lestari; Nurul Iman; Katni Katni (Universitas Muhammadiyah Ponorogo, 2019)
This study discusses Syed Muhammad Naquib al-Attas's Islamic education thinking that the concept of human education is different from other creatures, and only humans are educated. The meaning of tarbiyah is too wide in scope including growing, developing, training, feeding, and so on. This applies to animals and there is also no specialization for humans. Furthermore, eating ta'lim only lies on the cognitive. Of course the two terms are not in accordance with the purpose of Islamic education, namely education which gives birth to individuals who are Muslim. Education for humans is divided into 2 elements namely fardhu ‘ain and fardhu kifayah. Fardhu in ain is the religious sciences that instill spiritual every individual, where knowledge becomes the basis of humanity in practicing its knowledge in life. Then, fardhu kifayah is applied sciences to support the potential towards life skills to fulfill their needs as beings with needs (profession). The two sciences are inseparable, meaning that there is no separation between religion and the public. The science of religion is the basis of general science. In practice all the concepts and elements are included in the concept of ta'dib, wherein it not only teaches science but also educates, instills and forms noble humans. That is, a human being who can realize that Allah possesses only knowledge, so that by His mercy he is given knowledge.